Leveraging Generative AI for Sustainable Development: Opportunities, Risks and Ethical Pathways - Hamza Raza, Khan; Regalla Raghu, Raj; Aslam Raza, Khan; Nur Idayu, Badrolhisam (INTI International University, 2025)
Generative Artificial Intelligence (GenAI) is emerging as a transformative technology with great potential to advance the United Nations Sustainable Development Goals (SDGs). This paper presents a systematic review of recent research to examine how GenAI contributes to sustainable development in sectors such as education, healthcare, and governance. The study highlights the major opportunities offered by GenAI, including improved productivity, equitable access to information, and data-driven decision making that supports long-term sustainability. At the same time, it identifies critical risks such as high energy consumption, environmental impact, and ethical challenges related to fairness, transparency, and accountability. The review follows the PSALSAR framework to collect, evaluate, and synthesize existing evidence on the benefits and risks of GenAI. It also assesses emerging approaches to responsible AI governance that aim to create an inclusive and sustainable digital ecosystem. By balancing innovation with ethical responsibility, this study provides policy and research recommendations to guide the sustainable and equitable use of generative AI for global development.